The relationship between early childhood teachers' instructional quality and children's mathematics development. (December 2022) - Pohle, Lara; Hosoya, Georg; Pohle, Jennifer; Jenßen, Lars
Abstract: This study examined how early childhood (EC) teachers' instructional quality predicted children's development in mathematics across two measurement occasions. Therefore, EC teachers' ( n = 25) instructional quality was assessed using one standardized observation instrument covering both domain-specific and general aspects of instructional quality. Additionally, data on children's ( n = 208) outcome in early number skills was collected applying a standardized test. Multilevel structural equation modeling was used accounting for nested data. Children's age and the average size of preschool groups were controlled for. Results revealed that EC teachers' instructional quality predicted children's development but was not associated with their initial achievement. The findings suggest that instruments covering domain-specific and general aspects might be helpful in order to measure EC teachers' instructional quality in mathematics and predict children's learning growth. Understanding the mechanisms between instructional quality and children's development may help EC teachers to enhance their math teaching in practice. Highlights: Our sample consisted of more than 200 German children aged 2–6 years. A measure fitting countries with socio-pedagogical approaches to learning was used. The assessment covered general and domain-specific aspects of instructional quality. Instructional quality predicted children's mathematical development. It did not predict children's initial achievement levels in mathematics.